18F-FDG PET/CT findings of erythema induratum - KyungAh Chun, MD, PhD (Radiology Case Reports)
18F-FDG (fluorodeoxyglucose) accumulates in malignant tissues but also at the sites of infection and inflammation and in autoimmune and granulomatous diseases by the overexpression of distinct facultative glucose transporter (GLUT) isotypes (mainly GLUT-1 and GLUT-3) in cancer cells and inflammatory cells.A 75-year-old female with a history of skin rash with tenderness for 1 month underwent 18F-FDG positron emission tomography/computed tomography (PET/CT) to determine the presence of an underlying disease including malignant tumor. The 18F-FDG PET/CT showed hypermetabolic nodules at subcutaneous tissue (right upper arm, bilateral lower back and buttock, both thigh). She was diagnosed with erythema induratum on biopsy.